Prevalence of cataract, its risk factors and the barriers to cataract surgery among older women in a rural population of Cuddalore - Doss, Merlin S. J.; Kalyani, P.; Felix, A. John William (International Journal Of Community Medicine And Public Health, 2021)
Background: Cataract is the leading causes of vision impairment and preventable blindness in populations aged 50 and older. Advancing age, diabetes, hypertension, tobacco use and sunlight exposure are proven risk factors for cataract development. The prevalence of cataract is higher in low-income settings compared to high-income regions and also higher among females, compared to males. Hence this study has been conducted among a rural female population, aged 50 and above. Methods: The data collection for this descriptive cross-sectional study was conducted over a period of 4 months (December 2019 to March 2020), in a rural area of Chidambaram, Cuddalore. 397 study participants (202 females and 195 males) were interviewed using a semi-structured proforma, and examined accordingly. Of this, only the 202 females were included in this study, for estimating the prevalence of cataract among female population aged 50 and above. Data was analysed using SPSS statistical software presented as frequencies. Chi square test was used for finding association. Results: The overall prevalence of cataract in the present study is 64.9% (54.5% unilateral and 10.4% bilateral). Risk factors such as age, hypertension, diabetes, tobacco usage and sunlight exposure were significantly associated with the prevalence of cataract (p<0.05, 95% CI). Personal attitudinal reasons like neglect, no felt need and nobody to accompany were the most commonly encountered barriers to cataract surgery. Conclusions: Targeted camps, health education and screening programs can help overcome the unique barriers to surgery faced by females.